Physically Active Breaks in the Teaching Process : Impact on the Pupils" Educational Achievements = Tjelesno aktivni odmori u nastavi : utjecaj na obrazovna postignuća učenika - Holik, Ivan (Array, 2021)
The aim of this research is to study the impact of physically active breaks, accompanied by video materials, on the level of pupils" educational achievement and their attitudes toward physically active breaks during the teaching process in the classroom. The research lasted for two months, and the apposite sample consisted of a total of 38 pupils aged 10 to 11. The influence of physically active breaks on the educational achievement was estimated by the percentage of correct answers in the tasks of mathematics, while the Croatian version of the questionnaire Attitudes towards the Physical Activity Scale (APAS) was used for evaluating the attitudes toward physically active breaks with video materials. Differ ences between the initial and final measuring inside the same group were tested by the Student"s dependent sample t-test, while for differences between the experimental and control group the Student"s independent sample t-test was used. The obtained results showed that the ability to solve mathematical tasks in the experimental group has significantly improved when compared to the control one and that physically active breaks have a positive influence on the pupils" attitudes toward physical activity. The implementation of physically active breaks into teaching has an impact on pupils" productivity in the educational process, while at the same time their need for movement is fulfilled.